The Anti-nociceptive activity of a herbo-mineral and Siddha Nano formulation Linga Chenduram (LC) in selective pain induced models in Swiss albino mice - Soruban, Thiruvancheeswaran; S, Visweswaran (International Journal of Psychosocial Rehabilitation, 2020)
Background: The present study was aimed to investigate the anti-nociceptive activity of the Linga Chenduram in laboratory using the in vivo method so as to justify its traditional use in the above mentioned pathological conditions.Methods: In vivo anti-nociceptive activity was performed employing the hot plate method, test on Swiss albino mice at doses of 3 and 6 mg/kg body weight. Finally, data were analyzed by one-way analysis of variance (ANOVA) and Dunnett’s t-test was used as the test of significance. P value < 0.001 was considered as the minimum level of significance. Results: Linga chenduram at dose of 3 mg/kg is statistically not significance when compared to Vehicle control group. At 6 mg/kg, the drug showed anti-nociceptive activity with significance (P